Performance evaluation of sputter-coating based color BIPV modules under the outdoor operational condition: A comparative analysis with a non-color BIPV module - Hyomun Lee; Ruda Lee; Dongsu Kim; Jongho Yoon; Hyunil Kim; Gunhwan Lee (Energy Reports, 2022)
Building integrated photovoltaic (BIPV) modules with color-cover glasses have been developed to overcome design limitations in building applications. Although several current studies have presented informative outcomes through experimental analysis, understanding the long-term operating performance of color BIPV modules is still insufficient, especially when considering the transmittance features of the color-cover glass. Therefore, this study evaluates the operational performance of color BIPV modules based on comparative analysis under outdoor experimental conditions. A typical BIPV module (i.e., a non-color BIPV module) and color BIPV modules are used for this comparative analysis. The transmittance characteristics of general low-iron tempered glass (LTG) and LTG with the color coating are considered to evaluate the effect of performance degradation according to the transmittance reduction by the color coating. The thickness differences of the coating layer make different color patterns of gray, blue, and orange. In addition, the color modules are installed on the inclined (30°) and the vertical (90°) plane to assess power performance on different angle positions. Compared to the ratio of transmittance reduction (RTR) by the color coating and the percentage of efficiency reduction (RER) by the color-cover glass, the RER is less than the RTR. The RER of operational efficiency for blue and orange modules is similar to the RER in STC. Still, the RER of the gray module’s operational efficiency is about 5% greater than RER in STC. , the voltage and current characteristics for the gray module using operational data are analyzed to investigate the effect of color differences on the power efficiency. Based on the result, it was confirmed that the active efficiency reduction of the gray module is expected from the decrease in the current.